PENERAPAN METODE STRUCTURAL EQUATION MODELING UNTUK ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI AKADEMIK TERHADAP KUALITAS WEBSITE (Studi Kasus pada Website sia.undip.ac.id) - Enggar Nur Sasongko; Mustafid Mustafid; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Quality of website has an important role in giving effect to the website user's satisfaction. The quality of a website is measured by the adjusted WebQual dimensions include the dimensions of the system, dimension of information, dimension of interaction and dimension of services. Structural Equation Modeling is a method that used to examine complicated correlation simultaneously consisting of dependent variables and independent variables. This research aims to apply Structural Equation Modeling and Importance Performance Analysis methods in determining the influence of website quality factors on user satisfaction of academics Information System's website, and to find the performance of variables that need to be improved. This research is conducted at the University of Diponegoro, involving 200 students from Diponegoro University as the respondents. From the test of overall models, it obtained Goodness of Fit with the value of Chi Square = 68.748 and RMSEA = 0.084. From the analysis, it can be concluded that the dimension of interaction has the effect of 35%, dimension of information in amount of 35%, the dimension of service is 22.1%, and the dimensions of system in amount of 8.7%. And variables that need to improve performance are ease of website to be accessed's variable, variable of detail information, and ease of PBM evaluation's variable. Keywords: website quality, user satisfaction, Structural Equation Modeling